Foliar and edaphic parameters in a Quercus robur stand in Galicia (Spain) - Rozados Lorenzo, M. J.; Silva Pando, F. J.; Alonso Santos, M.; Ignacio Quinteiro, M. F. (Forest Systems, 2000)
Soil chemical composition during the active period was described in a oak stand (Quercus robur L.) situated at NW Iberian Peninsula. Leaves chemical composition and pigments were analysed on north and south-faced leaves in order to compare both positions. The parameters considered were: C, N, P, K, Ca, Mg, pH, ammonification and nitrification in soil and specific leaf weight (SLW), N, P, Ca, Mg, K, chlorophylls a and b and carotenoids in leaves. We focused on soil nitrification and ammonification processes to investigate nitrogen dynamic and to identify related factors. Significantly higher SLW was observed in south faced leaves than in north faced ones. There is a general trend in north faced leaves to show higher values of chlorophyll and carotenoids (per weight unit) and chlorophyll (per area unit), and in south-leaves to present higher nutrient concentrations, except phosphorus, and increased chlorophyll a/b. Nevertheless, any significant differences were found. The influence of environmental conditions on the soil was showed out by a decrease in C/N ratio in June and an increase in pH values in November.